Investigating the roles of relative sea-level change and glacio-isostatic adjustment on the retreat of a marine based ice stream in NW Scotland. (1st February 2022) - Simms, Alexander R.; Best, Louise; Shennan, Ian; Bradley, Sarah L.; Small, David; Bustamante, Emmanuel; Lightowler, Amy; Osleger, Dillon; Sefton, Juliet
Abstract: The record of ice-sheet demise since the last glacial maximum (LGM) provides an opportunity to test the relative importance of instability mechanisms, including relative sea-level (RSL) change, controlling ice-sheet retreat. Here we examine the record of RSL changes accompanying the retreat of the Minch Ice Stream (MnIS) of northwest Scotland during the deglaciation following the LGM as well as use the record to provide additional age constraints on a local late-glacial readvance known as the Wester Ross Readvance. We use new and existing records of RSL change obtained from isolation basins in Wester Ross along the flanks of the former MnIS to test available glacial-isostatic adjustment (GIA) predictions of the deglacial RSL history for the region. Using these GIA model predictions we examine the nature of RSL change across the retreating front of the MnIS through the early deglaciation. Our new radiocarbon ages from these basins confirm the timing of deglaciation within the inner trough of the former MnIS as well as refines the age of the Wester Ross Readvance, both established by earlier cosmogenic-based studies. We find that the Wester Ross Readvance culminated around 15.8 ± 0.1 ka, slightly earlier than recent suggestions. Near Gairloch, Wester Ross, RSL fell from a marine limit ∼20 m above present at ∼16.1–16.5 ka. Three isolation basins record RSL fall over the following ∼0.8 ka allowing a comparison between GIA predictions and RSL observations. Our new analyses suggest that the rate of RSL rise increased at the ice front, in concert with the MnIS encountering a landward sloping bed potentially aiding the rapid retreat of the MnIS from 17.6 to 16.4 ka BP. This observation suggests that GIA during deglaciation does not necessarily induce a stabilizing RSL change to marine-based ice streams as some models have suggested. Along indented ice margins, the RSL field at the front of individual ice streams may be governed by the regional GIA signal driven by the ice sheet as a whole, rather than the local ice front. In addition, the stabilizing impact of post-glacial rebound is dependent on an Earth rheology weak enough to respond quickly to the ice-sheet retreat. In the case of the MnIS, the RSL experienced at the front of the ice stream was likely governed by the earlier ice mass extent, the larger ice masses lying to the east and south of the highly indented ice front, and the relatively strong Earth rheology beneath the British Isles. Thus, the geometry of the ice sheet margins, such as those in Greenland and Antarctica today, and the Earth rheology beneath them need to be taken into account when considering the stabilizing impact of post-glacial rebound on marine ice sheet retreat. Highlights: Relative sea level (RSL) near Gairloch, NW Scotland, fell ∼20 m since 16.3 ± 0.2 ka. The Wester Ross Readvance occurred ∼15.8 ± 0.1 ka. RSL rise potentially contributed to the rapid retreat of the Minch Ice Stream. Post glacial rebound does not necessarily stabilize retreating marine ice sheets.